Characterization of vB_ValM_PVA8, a broad-host-range bacteriophage infecting Vibrio alginolyticus and Vibrio parahaemolyticus - Fu, Jingyun; Li, Ying; Zhao, Lihong; Wu, Chunguang; He, Zengguo (Frontiers in Microbiology, 2023)
Phage therapy was taken as an alternative strategy to antibiotics in shrimp farming for the control of Vibrio species of Vibrio parahaemolyticus and Vibrio alginolyticus, which cause substantial mortality and significant economic losses. In this study, a new Vibrio phage vB_ValM_PVA8 (PVA8) was isolated from sewage water and characterized by microbiological and in silico genomic analyses. The phage was characterized to be the Myoviridae family with elongated head and contractile tail by transmission electron microscopy. It could efficiently infect pathogenic isolates of V. alginolyticus and V. parahaemolyticus with a latent period of 20 min and a burst size of 309 PFUs/infected cell. It was noteworthy that phage PVA8 had minimum multiplicity of infection (MOI) of 0.0000001, which revealed its strong multiplication capacity. Genome sequencing showed that PVA8 had a 246,888-bp double-stranded DNA genome with a G+C content of 42.55%. It harbored totally 391 putative open reading frames (ORFs), among them 93 assigned to functional genes. Up to thirty-two transfer RNA (tRNA) genes were found in the genome, whereas the genes for virulence, antibiotic resistance and lysogeny were not detected. NCBI genomic blasting results and the phylogenetic analysis based on the sequences of the large terminase subunits and the DNA polymerase indicated that PVA8 shared considerable similarity with Vibrio phage V09 and bacteriophage KVP40. The phage was stable over a broad pH range (4.0-11.0) and a wide temperature span (-80℃ to 60℃), respectively, which may benefit its feasibility for phage therapy. The shrimp cultivation lab trials demonstrated that PVA8 could be applied in treating pathogenic V. parahaemolyticus infection disease of the shrimp, whereas the pond application trails confirmed that the implementation of PVA8 could rapidly yet effectively reduce the level of the Vibrio. Taken together, PVA8 may be potential to be explored as a promising biological agent for Vibrio control in aquaculture farming industry.